2004
DOI: 10.1002/mrm.20278
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous contrast agent improves sensitivity of gradient‐echo functional magnetic resonance imaging at 9.4 T

Abstract: Relative to common clinical magnetic field strengths, higher fields benefit functional brain imaging both by providing additional signal for high-resolution applications and by improving the sensitivity of endogenous contrast due to the blood oxygen level dependent (BOLD) mechanism, which has limited detection power at low magnetic fields relative to the use of exogenous contrast agent. This study evaluates the utility of iron oxide contrast agent for gradient echo functional MRI at 9.4 T in rodents using coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 28 publications
6
88
0
Order By: Relevance
“…At 7 T, 15-20 mg Fe/kg ultrasmall superparamagnetic iron oxides improve functional contrast-to-noise ratio (CNR) by 70% in rats compared with BOLD contrast [38]. Mandeville et al [39] reported that CNR in CBVweighted fMRI with 28 mgFe/kg improved twofold compared with BOLD upon pharmacological stimulation with cocaine. Even in humans, relatively high dosages of ultrasmall superparamagnetic iron oxides of 7 mgFe/kg have been used in fMRI acquisitions [40].…”
Section: Discussionmentioning
confidence: 99%
“…At 7 T, 15-20 mg Fe/kg ultrasmall superparamagnetic iron oxides improve functional contrast-to-noise ratio (CNR) by 70% in rats compared with BOLD contrast [38]. Mandeville et al [39] reported that CNR in CBVweighted fMRI with 28 mgFe/kg improved twofold compared with BOLD upon pharmacological stimulation with cocaine. Even in humans, relatively high dosages of ultrasmall superparamagnetic iron oxides of 7 mgFe/kg have been used in fMRI acquisitions [40].…”
Section: Discussionmentioning
confidence: 99%
“…The CBV fMRI measurements were obtained using a long half-life iron oxide contrast agent (ferumoxtran-10; Sinerem ® , Guerbet, France) to label the blood pool (Mandeville et al, 2004). A moderate increase (ca.…”
Section: Simultaneous Live O 2 and Cbv Fmri Monitoringmentioning
confidence: 99%
“…fMRI MR images were acquired repeatedly using a gradient echo EPI sequence with the IRON (Increased Relaxivity for Optimized Neuroimaging) technique [6,21] to assess relative cerebral blood volume (rCBV) changes. Since the rCBV measurement is insensitive to the magnetic field strength [21], data were acquired using both 4.7T and 9.4T MRI scanners (Bruker, Billerica, MA). Basic EPI parameters were: 16 segmentations, TR/TE of 625ms/6ms (a 10s/ volume temporal resolution), in-plane resolution of 0.2345mm × 0.2345mm, and 20 contiguous coronal slices, each 1 mm thick.…”
Section: Electrical Acupuncture (Ea)mentioning
confidence: 99%
“…Maps of rCBV responses were calculated on a pixel-by-pixel basis as described in [6,21]. The rCBV effect induced by AMPH and EA were characterized by two gamma functions (t*exp (-t/τ)) using general linear model (GLM), with time constant τ representing the peak time of the gamma curve.…”
Section: Electrical Acupuncture (Ea)mentioning
confidence: 99%